Nursing diagnoses in the climacteric and menopause period - Ohara, Elisabete Calabuig Chapina; Santos , Leticia de Araujo Farias dos; Santos , Luzinete Nunes dos (Seven Editora, 2023)
INTRODUCTION: The transition from the reproductive phase to the non-reproductive phase is considered a period with several changes. These changes can be metabolic and hormonal that have great reflections on the physiological and psychosocial aspect of this woman’s life, that is, she goes through physical and psychological changes. The symptoms in these phases are connected to biological, psychological and social factors, they present themselves in a unique way, varying according to the personal experiences of each woman. It is important in this non-reproductive phase of the woman that she can receive adequate care according to her needs. OBJECTIVE: To list the main nursing diagnoses, as well as nursing interventions in women’s health during climacteric and menopause. METHODOLOGY: This was an integrative literature review; the following databases were used to obtain data collection and selection of articles: Latin American and Caribbean Health Sciences Literature (LILACS), BDENF nursing (Brazil), Scientific Electronic Library Online (SCIELO) and Ministry of Health. The descriptors were Climacteric, Nursing, Care, Quality of life. The included articles published in full; in Portuguese, English and Spanish; published in the last 05 years and the articles excluded dissertations, theses and that did not answer the guiding question of the research. RESULTS: Applying the established criteria, nineteen (19) scientific articles were obtained for the integrative review. In the nursing consultation, it is possible to list the nursing diagnoses, which will increase the safety of women and improve the quality of care. Among the nursing diagnoses, we listed: Altered sexuality patterns; Knowledge deficit; Body image disorder; Sleep pattern disorder: Low self-esteem; Anxiety; Impaired skin integrity; Altered Comfort Risk for control; ineffective therapeutic regimen; Altered health maintenance and altered nutrition: risk greater than bodily needs. FINAL CONSIDERATIONS: The identification of nursing diagnoses contributes to the planning and execution of a nursing care plan directed to each woman, which is essential to obtain better quality of care. Some unhealthy symptoms reported by women in the non-reproductive phase can be relieved by nursing interventions that encourage changes in habits, such as quitting smoking, quitting alcohol, blood pressure control, weight control, healthy eating, restful sleep, leisure, and better self-esteem. DOI:https://doi.org/10.56238/interdiinovationscrese-020